Pediatric cardiologyStenting of the right ventricular outflow tract in a symptomatic newborn with tetralogy of Fallot - Dryżek, Paweł; Moszura, Tomasz; Góreczny, Sebastian; Michalak, Krzysztof W. (Advances in Interventional Cardiology/Postępy w Kardiologii Interwencyjnej, 2015)
This case describes a successful percutaneous stent implantation to critical stenosis of the right ventricle outflow tract in a female neonate with tetralogy of Fallot. At the time of the procedure she had poor development of the pulmonary arteries (McGoon and Nakata index 1.45 and 120, respectively). Stent implantation ensured an immediate increase in oxygen saturation level, and the physiological pulsating blood inflow caused good development of the pulmonary arteries during 12 months of follow up (McGoon 2.5; Nacata Index 436). After this time she was qualified for surgery and underwent surgical correction without using a patch or conduit implantation.